2014
DOI: 10.1021/jp4121673
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of Oxazole-Amino Acids: Effect of the Intramolecular N–H···N Hydrogen Bond

Abstract: Oxazole ring occurs in numerous natural peptides, but conformational properties of the amino acid residue containing the oxazole ring in place of the C-terminal amide bond are poorly recognized. A series of model compounds constituted by the oxazole-amino acids occurring in nature, that is, oxazole-alanine (L-Ala-Ozl), oxazole-dehydroalanine (ΔAla-Ozl), and oxazole-dehydrobutyrine ((Z)-ΔAbu-Ozl), was investigated using theoretical calculations supported by FTIR and NMR spectra and single-crystal X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…Additionally, one intramolecular hydrogen bond between the d ‐ allo ‐Ile amide N–H bond and the adjacent oxazole nitrogen atom to form a coplanar arrangement can be observed . This structural feature is also observed for urukthapelstatin A ( 1 ) as well as mechercharstatin ( 2 ) and might stabilize the conformation of the tripeptide . For other azoline‐containing cyclopeptides, it has been shown that this structural feature does not only exist in the solid‐state but is also retained in solution where it enhances the overall rigidity of a macrocycle , .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, one intramolecular hydrogen bond between the d ‐ allo ‐Ile amide N–H bond and the adjacent oxazole nitrogen atom to form a coplanar arrangement can be observed . This structural feature is also observed for urukthapelstatin A ( 1 ) as well as mechercharstatin ( 2 ) and might stabilize the conformation of the tripeptide . For other azoline‐containing cyclopeptides, it has been shown that this structural feature does not only exist in the solid‐state but is also retained in solution where it enhances the overall rigidity of a macrocycle , .…”
Section: Resultsmentioning
confidence: 87%
“…For urukthapelstatin A ( 1 ), this coplanarity is slightly distorted as the result of the steric hindrance caused by the additional methyl group of the dehydrobutyrine unit (Figure ). This reduced tendency for a coplanar conformation of the oxazole‐dehydrobutyrine unit compared to dehydroalanine has been studied for linear molecules before and seems to be displayed also by these macrocyclic peptides . As a result of the sp 3 ‐hybridization of the threonine residue in the cyclopeptides 30 and 31 , no coplanarity or hydrogen bond between the amide proton and the oxazole nitrogen atom is formed which might cause higher conformational flexibility of the tripeptide compared to the natural products 1 and 2 .…”
Section: Resultsmentioning
confidence: 97%
“…To date, nearly two dozen isoxazole‐containing pharmaceuticals, including semisynthetic β‐lactam antibiotics (e.g, oxacillin, dicloxacillin, flucloxacillin, and cloxacillin), sulfonamide antibacterials, antidepressants, antirheumatic drugs, anti‐inflammatory agents, antiviral drugs, fungicides, and hypoglycemic agents, have been approved by the FDA (Figure ). The use of conformationally restricted amino acids that contain heterocyclic rings for the preparation of peptidomimetics has recently been explored An interesting application in this field includes our recent reported on the preparation and use of 5‐aminoisoxazole restricted amino acids . This heterocyclic fragment is also present in the molecules of the above‐mentioned sulfonamide antibiotics (e.g., sulfametoxazole, sulfafurazole, and sulfisoxazole) as well as quirzatinib, which is currently under investigation for the treatment of acute myeloid leukemia …”
Section: Introductionmentioning
confidence: 99%
“…Amino acids found in nature undergo further structural modifications and recently oxazole structural motif gains considerable interest, including the design of new peptide analogs . In our previous work, the oxazole analogs of alanine, dehydroalanine, and ( Z )‐dehydrobutyrine were investigated and a strong tendency toward the conformation β2 stabilized by the intramolecular NH···N hydrogen bond was reported . Furthermore, the recent report shows that the modified Hantzsch reaction seems to be suitable method for the synthesis of oxazole‐dehydroamino acids, especially in case of ΔPhe .…”
Section: Introductionmentioning
confidence: 99%